Greener pastures : decentralizing the regulation of agricultural pollution - Brubaker, Elizabeth, 1958- (University of Toronto Centre for Public Management monograph series., 2007)
As farms increase in size and become increasingly industrialized, the problem of agricultural pollution is gaining urgency across Canada. The response from most environmentalists and provincial governments is to push for more centralized regulation. In Greener Pastures, Elizabeth Brubaker exposes the detrimental effects of such regulatory changes, which tend to exacerbate, rather than curb, pollution. For centuries, Brubaker explains, conflicts about farming were resolved by the parties directly involved, aided by common-law courts. The rule, 'use your own property so as not to harm another's, ' fairly and effectively resolved disputes between farmers and their neighbours and curbed environmental damage. Beginning in the 1970s, however, concerns about restraints on agriculture's growth prompted governments to replace the common law with more permissive provincial statutes. Greener Pastures chronicles the centralization of agricultural regulation and the resulting environmental harm. Brubaker focuses, specifically, on the right-to-farm laws (passed by every province in recent decades) that have freed farmers from common-law liability for the nuisances they create. She shows how these laws have made possible an unsustainable intensification of agriculture, and argues for a decentralized, rights-based decision-making regime. This thoroughly researched and impressively thought-out study challenges many common assumptions about environmental regulation, and proposes fresh answers to grave environmental and political questions.